Growth mechanism of strongly emitting CH3NH3PbBr3 perovskite nanocrystals with a tunable bandgap. Issue 1 (December 2017) - Huang, He; Raith, Johannes; Kershaw, Stephen; Kalytchuk, Sergii; Tomanec, Ondrej; Jing, Lihong; Susha, Andrei; Zboril, Radek; Rogach, Andrey
Abstract Metal halide perovskite nanocrystals are promising materials for a diverse range of applications, such as light-emitting devices and photodetectors. We demonstrate the bandgap tunability of strongly emitting CH3 NH3 PbBr3 nanocrystals synthesized at both room and elevated (60 °C) temperature through the variation of the precursor and ligand concentrations. We discuss in detail the role of two ligands, oleylamine and oleic acid, in terms of the coordination of the lead precursors and the nanocrystal surface. The growth mechanism of nanocrystals is elucidated by combining the experimental results with the principles of nucleation/growth models. The proposed formation mechanism of perovskite nanocrystals will be helpful for further studies in this field and can be used as a guide to improve the synthetic methods in the future. The development of perovskite nanocrystals is limited by poor mechanistic understanding of their growth. Here, the authors systematically study the ligand-assisted reprecipitation synthesis of CH3 NH3 PbBr3 nanocrystals, revealing the effect of precursor and ligand concentrations on bandgap tunability.